Chronic Post-operative Endophthalmitis caused by Acinetobacter Baumannii: A Case Presentation - Sodhi, Punita Kumari; Arya, Ayush; Aggarwal, Prabhav; Saxena, Sonal (Nepalese Journal of Ophthalmology, 2024)
Introduction: Endophthalmitis caused by Acinetobacter baumannii (A. baumannii) has been rarely reported in literature.Case: A case of chronic post-operative endophthalmitis (CPE) from A. baumannii is reported here. A 50-year-old hypertensive male did not gain good vision following implantation of a three-piece +20.0 diopter intraocular lens (IOL) in his left eye (LE). Five months later, he was referred to retina services with gross diminution of vision and whiteness of the cornea. An ultrasound B scan was done to assess the posterior segment. The pars plana vitrectomy could not be done due to corneal opacity. The specimen obtained from the anterior segment wash was sent for culture and sensitivity.Observation: The left eye (LE) had perception of light with an inaccurate projection of rays in all quadrants. On slit lamp examination, the cornea showed oedema, Descemet’s membrane folds, peripheral vascularisation and a blood-stained endothelium. The intraocular pressure (IOP), keratometry and axial length were 12 mmHg, 41.5 x 45.75 and 22.25 mm respectively. The ultrasound B scan showed a well-defined vitreous opacity with moderate to high echoes in the posterior segment pointing towards vitritis with IOL and cortical lens matter drop. There was choroidal detachment (CD) in one quadrant. The anterior segment specimen grew colonies of A. baumannii sensitive to co-trimoxazole, minocycline, and levofloxacin. Oral levofloxacin 750 mg once a day for ten days was prescribed, but his ocular condition did not improve. The IOP reduced to 8 mmHg, and a repeat ultrasound showed serous CD in two quadrants. Even with systemic steroids, inflammation did not resolve fully and LE had only perception of light one month later. Conclusion: A. baumannii should be kept as a differential diagnosis in cases of CPE. As it is multidrug resistant and therapeutic options are limited, endophthalmitis caused by this bacterium has a poor prognosis.